Clinical Outcome of Autoinoculation in the Management of Multiple Viral Warts: A Single-Arm Interventional Study - Noor Ul Huda; Sameena Kausar; Nasir Hussain; Ishtiaq Ahmed; Ghazala Yasmin; Tooba Hadia (Pakistan Journal of Health Sciences, 2026)
Autoinoculation is a relatively inexpensive immunotherapeutic treatment for viral warts, which is claimed to trigger a specific immune response. Objective: To determine the clinical outcome of autoinoculation, in terms of complete, partial, or no response, among patients presented with multiple viral warts. Methods: This is a single-arm interventional (quasi-experimental) study, which recruited 60 patients with multiple viral warts through non-probability sampling between March to October 2025. Autoinoculation was done by excision, mincing, and implantation of a donor wart into a pocket made in the subcutaneous area. Follow-ups were made monthly following initiation of treatment, and outcome measured at 12 weeks in terms of complete, partial, or no response. SPSS version 25.o was used to perform a statistical analysis. Chi-square tests and ordinal logistic regression were used to determine significant associations and to derive adjusted ORs. Results: Study results illustrate that 73.3% (n=44) of patients achieved a complete response, 15.0% (n=9) a partial response, and 11.7% (n=7) showed no response. Mean number of warts reduced significantly from 7.7 (pre-treatment) to 1.75 (post-treatment). Stratification analysis revealed a significant association of age with treatment outcome (p=0.031). Patients in the age group 15-30 years showed the highest rate of complete response. No other demographic or clinical factors demonstrated a significant association. Conclusions: Autoinoculation is a considerable practicing, safe and effective therapeutic modality in treating various viral warts. Its better results among young patients highlight the critical role of a strong immune system in the implementation of its therapeutic action.